A ray‐tracing algorithm for ab initio calculation of thermal load in undulator‐based synchrotron beamlines. (14th July 2020) - Rebuffi, Luca; Shi, Xianbo; Sanchez del Rio, Manuel; Reininger, Ruben
Abstract : The OASYS suite is used to implement a ray‐tracing algorithm to calculate the thermal load in undulator‐based synchrotron beamlines. The algorithm is particularly suited to analyze cases with complex beamline layout and optical elements. Examples of its use on two of the feature beamlines at the Advanced Photon Source Upgrade Project are shown. Abstract : The OASYS suite and its powerful integration features are used to implement a ray‐tracing algorithm to accurately calculate the thermal load in any component of an undulator‐based synchrotron beamline. This is achieved by sampling and converting the SRW source of a given energy into a Shadow source and using the latter code to ray trace the full beamline. The accuracy of the algorithm is proved by reconstructing the full undulator radiation distribution through an aperture and comparing the result with direct calculaton of the total power using  SRW . The algorithm is particularly suited to analyze cases with complex beamline layouts and optical elements, such as crystals, multilayers, and compound refractive lenses. Examples of its use to calculate the power load on elements of two of the feature beamlines at the Advanced Photon Source Upgrade Project and a comparison of the results with analytical calculations are presented.